Cultural Representation in English Textbook Produced By English Course in Pesantren - Prajabka, Gita Utari; Dwi Andriani, Zulfi Zumala; Fadly, Ahmad Mufarih Hasan (Yayasan Keluarga Guru Mandiri, 2025)
This study examines cultural representations in two English books used by pesantren educational institutions, the English Conversation Club (ECC) and the English Learners Association (ELA) at Pesantren Darussalam Blokagung. This study used a qualitative approach with a descriptive approach. Data collection was conducted through content analysis and interviews. Informant sources include textbook writers and English course instructors. In contrast, the data analysis used Miles and Huberman's data reduction, data analysis, and inference simulation techniques. The results showed that the textbook contained four cultural values: tolerance, equality, justice, and democracy. The value of tolerance is shown in the interaction between people from different cultures. The value of equality is shown in the inclusive delivery of materials. Both informative texts, conversations, and opinion writing exercises demonstrate fairness, and texts that emphasize balance in decision-making demonstrate a democratic approach. Textbooks do two things: they help students learn the language and 3protect the culture of boarding schools around the world. To help students become confident and culturally sensitive communicators in the era of globalization, this study suggests the creation of relevant teaching materials.